Lithium cobalt(II) pyrophosphate, Li(1.86)CoP(2)O(7), from synchrotron X-ray powder data - Zhou, Hui (International Union of Crystallography, 2011)
Structure refinement of high-resolution X-ray powder diffraction data of the title compound gave the composition Li(1.865)CoP(2)O(7), which is also verified by the ICP measurement. Two Co sites exist in the structure: one is a CoO(5) square pyramid and the other is a CoO(6) octahedron. They share edges and are further interconnected through P(2)O(7) groups, forming a three-dimensional framework, which exhibits different kinds of intersecting tunnels containing Li cations and could be of great interest in Li ion battery chemistry. The structure also exhibits cation disorder with 13.5% Co residing at the lithium (Li1) site. Co seems to have an average oxidation state of 2.135, as obtained from the strutural stochiometry that closely supports the magnetic susceptibility findings.